2008
DOI: 10.1080/13548500701405517
|View full text |Cite
|
Sign up to set email alerts
|

Restlessness and psychomotor agitation after kidney transplantation: Their impact on perceived health status

Abstract: Restlessness and psychomotor agitation are among the causes of morbidity and mortality in different diseases. They are known problems in end-stage renal disease patients but no study has ever evaluated their presence and effects in kidney recipients. This study aimed to explore the presence of restlessness and psychomotor agitation and their relation with morbidity of patients after renal transplantation. Sixty-one subjects were randomly selected from kidney transplant recipients being followed in Baqiyatallah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…43 The positive relationship between mood and total wake time suggests that pre-KTX participants experienced greater insomnia symptoms concurrent with worse mood and is consistent with previous research. 13,14,23 This relationship may be the result of worse sleep resulting in greater mood disturbance, worse mood impairing sleep or a third factor impacting both mood and sleep. While the relationship between these two factors was clearly present, further research is needed to determine the causal relationship.…”
Section: -6mentioning
confidence: 99%
See 2 more Smart Citations
“…43 The positive relationship between mood and total wake time suggests that pre-KTX participants experienced greater insomnia symptoms concurrent with worse mood and is consistent with previous research. 13,14,23 This relationship may be the result of worse sleep resulting in greater mood disturbance, worse mood impairing sleep or a third factor impacting both mood and sleep. While the relationship between these two factors was clearly present, further research is needed to determine the causal relationship.…”
Section: -6mentioning
confidence: 99%
“…7,10,11 Comorbidity rates between poor sleep, ESRD and psychological distress, particularly anxiety and depression (~60% of dialysis patients), are also high. 12,13 ESRD patients who have elevated depressive symptoms report increased difficulty falling asleep, staying asleep, waking too early in the morning, and increased fatigue in the morning. 14 Quality of life is often compromised among individuals suffering from chronic health conditions such as insomnia and ESRD.…”
Section: Scientific Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature demonstrated the scarce number of studies conducted at hospital psychiatric wards and the difficulty in the assessment of the quality of the programs, services, and results of medical care [ 17 ], with differences found in the use of guides among centers and where even acute stress, such as a transplant, could be a trigger [ 34 ]. Future research should focus on the use of programs and homogenous guides such as the WHO Quality Rights Toolkit [ 35 ] between countries to reduce mechanical restraint [ 6 ].…”
Section: Discussionmentioning
confidence: 99%